Outcome of hematopoietic stem cell transplantation as salvage therapy for pediatric relapsed/refractory hodgkin lymphoma: A single center experience - Anak, Seniye Sema; Yaman, Yöntem; Elli, Murat; Sarıbeyoğlu Tuğrul, Ebru; Hazar, Volkan; Özdilli, Kürşat (Wiley, 2018)
[Abstract Not Available]
WOS: 000445195002021